[BP.04.05] PREVALENCE AND CLINICAL PHENOTYPE OF PRIMARY ALDOSTERONISM IN PRIMARY CARE HYPERTENSIVES. (September 2017) - Monticone, S.; Burrello, J.; Tizzani, D.; Bertello, C.; Viola, A.; Buffolo, F.; Williams, T.A.; Rabbia, F.; Veglio, F.; Mulatero, P.
Abstract : Objective: Despite being widely recognized as the most common form of secondary hypertension, the true prevalence of primary aldosteronism (PA) and its main subtypes, aldosterone-producing adenoma (APA) and bilateral adrenal hyperplasia (BAH), among the general hypertensive population remains a matter of debate. The present study was undertaken to determine the prevalence and clinical phenotype of PA in a large cohort of unselected hypertensive patients, consecutively referred to our Hypertension Unit, by 19 general practitioners. Design and method: Patients were screened for PA using the serum aldosterone to plasma renin activity ratio after withdrawal from all interfering medications and PA was diagnosed according to the Endocrine Society guidelines. The diagnosis was confirmed/excluded by an i.v. saline infusion test or captopril challenge test and subtype differentiation was performed by adrenal CT scanning and adrenal vein sampling (AVS) using strict criteria to define both successful cannulation and lateralization of aldosterone production. Results: A total of 1, 672 primary care hypertensive patients, 569 newly diagnosed hypertensives and 1, 103 patients already diagnosed with arterial hypertension, were included in the study. A total of 99 patients (5.9%) were diagnosed with PA and conclusive subtype differentiation by AVS was made in 91 patients (27 patients with an APA and 64 patients with BAH). The overall prevalence of PA increased with the severity of hypertension, from 3.9% in hypertensives stage I to 11.8% in hypertensives stage III. Patients with PA more frequently displayed target organ damage and cardiovascular events compared to non-PA hypertensives, independent of confounding variables. Conclusions: The results from the present study demonstrated that PA is a frequent cause of secondary hypertension even in the general hypertensive population and indicates that the majority of hypertensive patients should be screened for PA.